2022
DOI: 10.1186/s12904-022-01040-0
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in palliative care for patients with common non-cancer diseases: a cross-sectional study

Abstract: Background Non-cancer patients experience the chronic process of disease that increases the patients’ suffering as well as families’ care burden. Although two-thirds of deaths are caused by non-cancer diseases, there is a lack of studies on palliative care for non-cancer patients. This study identified the palliative care needs and satisfaction, anxiety and depression, and health-related quality of life (HRQOL) of non-cancer patients and identified the factors influencing their HRQOL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…It may also reflect the fact that SPC supports have traditionally been more focused on cancer diagnoses, and there is greater capacity to manage care needs at home. 20 , 33 Cancer diagnosis may be capturing some of the system-level influence in our data.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It may also reflect the fact that SPC supports have traditionally been more focused on cancer diagnoses, and there is greater capacity to manage care needs at home. 20 , 33 Cancer diagnosis may be capturing some of the system-level influence in our data.…”
Section: Discussionmentioning
confidence: 96%
“…It may also reflect the fact that SPC supports have traditionally been more focused on cancer diagnoses, and there is greater capacity to manage care needs at home. 20,33 Cancer diagnosis may be capturing some of the systemlevel influence in our data. -The significant association between prior hospital use and hospital death, and between prior hospital use and noncongruence, could be capturing residual complexity of need.…”
Section: Key Lessonsmentioning
confidence: 99%
“…Part 2 evaluated health-related quality of life (HRQOL). HRQOL was measured using the Chinese version of the Medical Outcome Study 36-item Short Form Health Survey (MOS SF-36) [9,10]. The MOS SF-36 consists of 36 items covering 8 areas, namely, physical function, physical roles, physical pain, overall health status, vitality, social function, emotional roles, and mental health.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…Most older adults severely affected by noncancer conditions experience progressive functional disability and subsequent health decline during the course of their disease. Moreover, some studies reported that functional status is significantly associated with health-related QOL (HRQOL) in people with noncancer conditions [118,119]. Although disease-specific functional assessment measures can be available in some noncancer diseases, the Australia-modified Karnofsky Performance Status (AKPS) is a modified version for palliative care that is widely used and appropriate for multiple care settings in palliative care populations [120].…”
Section: Functional Status and Quality Of Lifementioning
confidence: 99%